2015
DOI: 10.1073/pnas.1506282112
|View full text |Cite
|
Sign up to set email alerts
|

FUS functions in coupling transcription to splicing by mediating an interaction between RNAP II and U1 snRNP

Abstract: Pre-mRNA splicing is coupled to transcription by RNA polymerase II (RNAP II). We previously showed that U1 small nuclear ribonucleoprotein (snRNP) associates with RNAP II, and both RNAP II and U1 snRNP are also the most abundant factors associated with the protein fused-in-sarcoma (FUS), which is mutated to cause the neurodegenerative disease amyotrophic lateral sclerosis. Here, we show that an antisense morpholino that base-pairs to the 5′ end of U1 snRNA blocks splicing in the coupled system and completely d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
83
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(90 citation statements)
references
References 43 publications
6
83
0
Order By: Relevance
“…16 Recent in vitro analysis using the HeLa cell nuclear extracts has revealed that FUS couples transcription with splicing by mediating an association between RNAP II and U1 snRNP. 61 FUS may be an intermediate factor that links transcription and splicing (Figure 3). …”
Section: Alternative Splicingmentioning
confidence: 99%
“…16 Recent in vitro analysis using the HeLa cell nuclear extracts has revealed that FUS couples transcription with splicing by mediating an association between RNAP II and U1 snRNP. 61 FUS may be an intermediate factor that links transcription and splicing (Figure 3). …”
Section: Alternative Splicingmentioning
confidence: 99%
“…FUS is a DNA- and RNA-binding protein with evidence for functions in DNA repair, transcriptional regulation, alternative splicing regulation, RNA localization, and association with stress granules (Sama et al, 2014). FUS has also been shown to couple transcription to alternative splicing by interacting with both RNA polymerase II and U1 snRNP (Yu and Reed, 2015). Homozygous knockout of Fus produces perinatal lethality in inbred mouse lines (Hicks et al, 2000).…”
Section: Fus and Tdp-43 In Alsmentioning
confidence: 99%
“…In addition to a direct alteration on this process, ALS-related mutations may affect also the network of protein-protein interaction of FUS and TDP-43 with other splicing factors. Indeed, FUS interacts with both RNA polymerase II and the small nuclear ribonucleoprotein complex snRNP U1, thus suggesting that it might have a role in coupling transcription to splicing (143). Moreover, FUS and TDP-43 interact with the SMN complex, which is essential for spliceosome assembly (132,140) and mutant FUS sequesters both SMN and snRNPs in protein aggregates in the cytoplasm, leading to alteration in the alternative splicing process (45,142).…”
Section: Tdp-43 and Fus: Rna Dys-metabolism As A Novel Player In Alsmentioning
confidence: 99%